2018
DOI: 10.1016/j.foodchem.2018.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of thermal and non-thermal processing effect on non-prebiotic and prebiotic acerola juices using 1 H q NMR and GC–MS coupled to chemometrics

Abstract: The effects of thermal (pasteurization and sterilization) and non-thermal (ultrasound and plasma) processing on the composition of prebiotic and non-prebiotic acerola juices were evaluated using NMR and GC-MS coupled to chemometrics. The increase in the amount of Vitamin C was the main feature observed after thermal processing, followed by malic acid, choline, trigonelline, and acetaldehyde. On the other hand, thermal processing increased the amount of 2-furoic acid, a degradation product from ascorbic acid, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 37 publications
(41 reference statements)
1
29
0
1
Order By: Relevance
“…On the whole, the main components of the terpenes, alcohols, and esters (such as ethanol, 3-methyl-4-oxopentanoic acid, hexanal, (E)-2-hexenal, 1-hexanol, hexanoic acid, and ethyl ester) in CK were significantly higher than those in other three groups, which indicated that the sterilization methods in this experiment significantly reduced the contents of the main volatile components in the grape juice. Similar conclusions were also observed in Filho et al [ 51 ]. In addition to the reduction in the contents of the main volatile components, sterilization treatment also resulted in the formation of some new substances.…”
Section: Resultssupporting
confidence: 92%
“…On the whole, the main components of the terpenes, alcohols, and esters (such as ethanol, 3-methyl-4-oxopentanoic acid, hexanal, (E)-2-hexenal, 1-hexanol, hexanoic acid, and ethyl ester) in CK were significantly higher than those in other three groups, which indicated that the sterilization methods in this experiment significantly reduced the contents of the main volatile components in the grape juice. Similar conclusions were also observed in Filho et al [ 51 ]. In addition to the reduction in the contents of the main volatile components, sterilization treatment also resulted in the formation of some new substances.…”
Section: Resultssupporting
confidence: 92%
“…NMR spectroscopy has been used for the quality control of foods in terms of monitoring stability (Alonso‐Salces, Holland, & Guillou, ; Guillen & Goicoechea, ; Lamanna, Piscioneri, Romanelli, & Sharma, ; Souza, Martínez, Ferreira, & Kaiser, ), storage history (Belloque et al., ; Fronimaki et al., ; Graham et al., ), packaging (Pentimalli et al., ), safety (Beer et al., ; Marchand et al., ; Monakhova, Kuballa, & Lachenmeier, ), evaluation of agronomic practices (Consonni et al., ; Gallo et al., ; Jahangir et al., ; Winning et al., ; Zhang, Breksa, Mishchuk, & Slupsky, ), and studying process‐induced effects (Alves Filho et al., ; García‐García, Lamichhane, Castejón, Cambero, & Bertram, ; Lopez‐Sanchez et al., ; Sinanoglou et al., ; Vermathen et al., ; Wakamatsu, Handa, & Chiba, ; Zoumpoulakis et al., ; Hwang et al, ). Characteristic examples of foods include fish (Erikson et al., ; Martinez et al., ; Tan et al, ), meat (Straadt, Aaslyng, & Bertram, ), spices (Cagliani, Culeddu, Chessa, & Consonni, ; Ordoudi et al., ), beverages (Almeida et al., ; Le Gall, Colquhoun, & Defernez, ; Spevacek, Benson, Bamforth, & Slupsky, ; Walch, Stühlinger, Lachenmeier, Monakhova, & Kuballa, 2012a), oils (Lucas‐Torres, Pérez, Cabañas, & Moreno, ), and dairy products (Maher & Rochfort, ; Shintu & Caldarelli, ).…”
Section: Fundamentals Of Nmr Spectroscopy‐relevance To Food Sciencementioning
confidence: 99%
“…PCA scores (A), and loadings (B) plots of acerola juices upon various processings: Cont, control; HTST, pasteurized; UHT, sterilized; Plas.10, 10 min of plasma treatment; Plas.20, 20 min of plasma treatment; US.5, 5 min of ultrasound application; US.15, 15 min of ultrasound application. (Reprinted from Alves Filho et al., , with permission from Elsevier).…”
Section: Fundamentals Of Nmr Spectroscopy‐relevance To Food Sciencementioning
confidence: 99%
“…The growing market of functional foods, associated with the highly perishable nature of ripe fruits, has been pushing food industry to develop new product‐oriented technologies in order to best exploit the dietary and therapeutic value of fruit (Belwal et al, ; Moura et al, ). Frozen fruit and pulps (Vergara, Reissig, Franzon, Rodrigues, & Chim, ), prebiotic fortification of juice (Alves Filho et al, ), flavored beverages (Cappato et al, ) and powdered food ingredients (Correia, Grace, Esposito, & Lila, ; de Moraes, Gonçalves, Miguel, Borges, & Correia, ) are among the processing strategies for increasing the alternative consumption of fruits.…”
Section: Introductionmentioning
confidence: 99%
“…Frozen fruit and pulps (Vergara, Reissig, Franzon, Rodrigues, & Chim, 2018), prebiotic fortification of juice (Alves Filho et al, 2018), flavored beverages (Cappato et al, 2018) and powdered food ingredients (Correia, Grace, Esposito, & Lila, 2017;de Moraes, Gonçalves, Miguel, Borges, & Correia, 2017) are among the processing strategies for increasing the alternative consumption of fruits.…”
Section: Introductionmentioning
confidence: 99%